Quando os assentados chegaram: tempo e experiência social no MST - Mello, Marcos Paulo Campos Cavalcanti de (2011)
The central question of this study is understand how rural workers members of the Movement of Landless Workers (MST) reconstruct the social experience of their first land occupation in the Ceara with reference of time. Therefore, the interpretation aims to understand the logics that organize the meanings attributed to the past expressed in the statements of its protagonists and the political ritualization of the event prepared by the MST. Accordingly, the focus is on memory by reference to occupation realized by the Movement in Ceará in May 1989 on land owned by General Wicar Parente Paula Pessoa called Fazendas Reunidas São Joaquim located in the municipality of Madalena in the region of Central Hinterland Ceará. The speech of the occupation’s participants reconstruct its organizational experience through discursive elaborations operating the establishment of time frames that are linked to various social processes, such as schemes of work and production, sociability, ownership structure, religion and political participation. In this sense, the accounts of individuals surveyed indicate two different times of the occupation occurred in 1989, they are: The time of the farmer and When the settlers arrived. The first temporality limited social relationships before the occupation and relates to the traditional system of political domination, forms of subjection of labor in large land holdings and small-scale agricultural production in smallholdings inherent in rural areas of Ceara in 1980. By other hand, the second temporality adds a pastoral temporality of Christianity of liberation, social conflicts between employers and domestic workers to the farms, the union activity, social mobilization for the implementation of the occupation, the arrival of the occupants of the property, the moment of the camp and the establishment of the settlement on 25 de Maio. The rural workers participating in the process on focus symbolically elaborate their social experience in a ritual named mística. On this ritual, the memory of the first occupation of land in Ceará realized by the MST is appropriated in a speech about exaltation and occultation allowed by members of the Movement as a legitimate form of enunciation of the event. The discourse of remembrance embodies a function justifying the actions of resistance in a reference to a past working in the social construction of time in reference to an event perceived as a founder: the occupation.